Factors Affecting the Successful Implementation of E-Government on Network Documentation and Legal Information Website in Riau - Muhammad Ikhsan Wibowo; Albertus Joko Santoso; Djoko Budiyanto Setyohadi (Bina Nusantara University, 2018)
Network documentation and legal information website is a form of e-government applications such as Jaringan Dokumentasi dan Informasi Hukum (JDIH). JDIH website must be designed to be an effective and efficient information system. This study aims to determine the success factors of the implementation of JDIH website. The DeLone and McLean model and the Unified Theory Acceptance and Use of Technology (UTAUT) are the models used in this study. The case study is conducted in the Riau legal and human rights office. Data are obtained through questionnaires from 252 respondents in the Riau provincial government and some communities. The analysis uses Structural Equation Modeling (SEM) and Analysis of Moment Structure (AMOS). The results of this study show that nine hypotheses have positive effects. Meanwhile, four hypotheses have no positive effects on the success and use of JDIH website. The findings of this research will be used as a reference inthe development of JDIH website in the future.